1993
DOI: 10.1007/bf00599616
|View full text |Cite
|
Sign up to set email alerts
|

Volume changes in the lower leg during quiet standing and cycling exercise at different ambient temperatures

Abstract: The purpose of this study was to investigate whether ambient temperature influences both the rate of leg swelling during orthostasis and the oedema-preventing effect of the skeletal muscle pump. Using mercury-in-rubber strain gauges, volume changes were measured in the calf (n = 34) and near the ankle (n = 24) in healthy volunteers aged 19-33 years. Measurements were performed during 12 min of motionless standing in an upright posture and during 17 min of cycle exercise at intensities of 50 W and a pedalling r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…This correlation was no longer significant after adjustment for BMI. However, many studies defining leg volume as an endpoint report absolute or relative leg volume differences between different measurement time points [3,23,24,27]. Our data indicate that variation of the exact daytime of volumetry measurements at the different visits features a highly significant linear correlation between the time difference and the leg volume difference, even after adjustment for possible confounders such as the BMI.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…This correlation was no longer significant after adjustment for BMI. However, many studies defining leg volume as an endpoint report absolute or relative leg volume differences between different measurement time points [3,23,24,27]. Our data indicate that variation of the exact daytime of volumetry measurements at the different visits features a highly significant linear correlation between the time difference and the leg volume difference, even after adjustment for possible confounders such as the BMI.…”
Section: Discussionmentioning
confidence: 67%
“…This could potentially represent a lack of reliability; however, we strongly suggest a rapid orthostatic leg volume change to explain this observation. Several previous studies observed a rapid increase of leg volume when body position is changed from a supine to a sitting or standing position [10,27-29], with no difference between healthy and varicose legs [10,28]. After changing position from lying to sitting/standing, Stick et al reported a two-stage change in calf volume with a fast initial increase followed by a slow continuous volume increase [30].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the baroreflex effect may increase the calf volume at a given venous pressure less during HUT than during thigh occlusion, although the effect of whole-body thermal stress on the In the present study, the change in calf volume includes the change in the extravascular fluid volume with a transcapillary fluid shift in addition to the venous volume, although the duration (4 min) of HUT was comparatively short as a general orthostatic stress. With regard to the transcapillary fluid shift in the upright posture, Stick et al (1993) have reported that the change in leg volume due to capillary filtration during a period of 2 min to 12 min of quiet standing was not affected by ambient temperature in the range of 20-36°C. Diaz et al (1979) found that the decrease (17.3%) in plasma volume in the upright posture for 45 min in a hot environment (49.5°C) was only 2-3% greater than that in a cool environment.…”
Section: Methodological Considerationsmentioning
confidence: 98%
“…In contrast, short breaks of up to 5 min ® lled with either dynam ic activity or rest did not signi® cantly aOE ect leg swelling in the study by Dupuis and Rieck (1980). It has been shown that, except for the swelling occurring during the ® rst 2 min after verticalization, swelling and recovery of swelling are slow processes, which do not level oOEwithin about 15 min (Stick et al 1993). Thus it can be understood that increasing the duration of a break 15 min, or in contrast increasing shift duration > 30 min, does aOE ect the swelling, whereas short breaks do not have a discernible eOE ect.…”
mentioning
confidence: 98%